Impact of digital learning tools on numeracy, motivation, and engagement in elementary education - Ardono Ardono; Juharyanto Juharyanto; Slamet Arifin (Journal of Research in Instructional, 2026)
This study investigated the effects of digital technology–integrated mathematics instruction on elementary students' numeracy achievement, learning motivation, classroom engagement, and technology acceptance. A quasi-experimental non-equivalent control group design was employed involving two Grade VI classes (N = 50) from an elementary school in Tanah Tidung Regency, Indonesia. Data were collected using numeracy pretests and posttests, an ARCS-based learning motivation questionnaire, a Technology Acceptance Model (TAM) questionnaire, a classroom engagement observation sheet, and an implementation fidelity checklist. Prior to hypothesis testing, data were examined using the Shapiro–Wilk and Levene's tests. The data were subsequently analyzed using independent samples t-tests, analysis of covariance (ANCOVA), normalized gain (N-Gain), and Cohen's d effect size. The results showed that the experimental group achieved significantly higher numeracy performance than the control group, as reflected by higher posttest scores, a greater normalized gain (0.57 vs. 0.26), and a very large effect size (d = 1.99). ANCOVA further confirmed that the improvement remained significant after controlling for students' initial numeracy ability. Students in the experimental group also demonstrated significantly higher learning motivation across all ARCS dimensions, stronger classroom engagement, and high levels of technology acceptance. These findings indicate that integrating digital technology into mathematics instruction enhances students' cognitive achievement while simultaneously promoting positive motivational and behavioral learning outcomes. The study provides practical evidence supporting the implementation of technology-enhanced mathematics instruction in elementary education, particularly in rural school contexts.